Fast divalent conduction in MB12H12·12H2O (M = Zn, Mg) complex hydrides: effects of rapid crystal water exchange and application for solid-state electrolytes. Issue 46 (18th November 2022) - Kisu, Kazuaki; Dorai, Arunkumar; Kim, Sangryun; Hamada, Riku; Kumatani, Akichika; Horiguchi, Yoshiko; Sato, Ryuhei; Sau, Kartik; Takagi, Shigeyuki; Orimo, Shin-ichi
Abstract : Water molecules are exchanged in the crystal structure, which imparts a high divalent conductivity to hydrated complex hydrides. MB12 H12 ·12H2 O (M = Zn or Mg) exhibits exceptional conductivities higher than those of less-hydrated complex hydrides. Abstract : This work investigates the divalent conduction of Zn 2+ and Mg 2+ in hydrated closo-type complex hydrides MB12 H12 · n H2 O (M = Zn, Mg) and the effects of crystal water exchange in the structure for enhancing divalent ionic conduction. MB12 H12 · n H2 O (M = Zn, Mg), which exhibited different hydrous phases, was synthesised as a single phase and characterised using X-ray diffraction and Raman spectroscopy for determining the number of crystal water molecules and the cationic water coordination environment. Among the anhydrous and hydrated MB12 H12 · n H2 O ( n = 0–12 and M = Zn, Mg), ZnB12 H12 ·12H2 O and MgB12 H12 ·12H2 O exhibited exceptional ionic conductivities of 3.8 × 10 −5 and 6.1 × 10 −5 S cm −1 at 50 °C, respectively, thereby being of greater significance than less-hydrated MB12 H12 · n H2 O ( n ≤ 6), and a few of the highest solid-state Zn 2+ and Mg 2+ conductivities reported so far. 1 H, 11 B, and 67 Zn NMR measurements show narrow peaks indicating rapid crystal water exchange, fast [B12 H12 ] 2− anion rotation, and rapid Zn 2+ isotropic motion in ZnB12 H12 ·12H2 O. Electrochemical cells fabricated using the ZnB12 H12 ·12H2 O solid electrolyte exhibited reversible Zn 2+ migration through the material, indicating that ZnB12 H12 ·12H2 O shows favourable potential for application as a Zn 2+ conductor in all-solid-state Zn batteries.